Cross-cultural differences in children's concepts of health and illness - Boruchovitch Evely; Mednick Birgitte R. (Universidade de São Paulo, 1997)
INTRODUCTION: In spite of general agreement that cross-cultural research is needed in the health area, most existing investigations of children's development of health and illness-related concepts have involved samples from developed countries. The study examined the development of the concepts of health and illness as a function of subject's age, socio-economic status (SES), gender and grade level in a Brazilian sample of 96 elementary and junior high school students. METHODS: Subjects were interviewed individually and their ideas of health and illness were assessed through open-ended questions. Participants' answers were transcribed verbatim and subjected to content analysis. RESULTS: Chi-square analyses revealed significant age, school grade and SES-related differences in participants' concepts of health and illness. DISCUSSION AND CONCLUSION: The themes employed by subjects to define both health and illness were broadly consistent with those found by previous research. The study showed a predictable relationship between subject's age and school grade level and increasingly more highly differentiated and multidimensional concepts of health and illness. This investigation suggests that, for the most part, cross-cultural similarities in children's concepts of health and illness may be more striking than the differences.